1991
DOI: 10.1002/cem.1180050305
|View full text |Cite
|
Sign up to set email alerts
|

Examining large databases: A chemometric approach using principal component analysis

Abstract: Principal component analysis is used to examine large multivariate databases. The graphical approach to exploratory data analysis is described and illustrated with a single example of chemical composition data obtained on environmental dust particles. While the graphical approach to exploratory data analysis has certain advantages over the numerical procedures, the empirical approach described here should be viewed as complementary to the more robust treatments that statistical methodologies afford.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 6 publications
1
42
0
2
Order By: Relevance
“…PCA score plotting is a very good tool for identifying outliers, influential points, and data entry errors. 60 Figure 3A shows that 7 of the 25 026 compounds appeared at the extremes. By checking the original database, we found that the GI 50 values of the four compounds (NSC numbers 619989, 620130, 624589, and 626674) located at the upper left corner of Figure 3A were simply miscoded in the database: the exponents of concentrations that should have been -4 or -6 were miscoded as +4 or +6.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
See 2 more Smart Citations
“…PCA score plotting is a very good tool for identifying outliers, influential points, and data entry errors. 60 Figure 3A shows that 7 of the 25 026 compounds appeared at the extremes. By checking the original database, we found that the GI 50 values of the four compounds (NSC numbers 619989, 620130, 624589, and 626674) located at the upper left corner of Figure 3A were simply miscoded in the database: the exponents of concentrations that should have been -4 or -6 were miscoded as +4 or +6.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
“…Meglen has given an excellent description of the use of PCA to examine large databases. 60 Koutsoukos et al 21 have used PCA to analyze the NCI cell screen data for a set of 141 "standard" anticancer agents for which the mechanisms of action are well-defined. 20 PCA score plots showed distinct clusters of compounds for some of the mechanisms of action examined.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
See 1 more Smart Citation
“…Here it is demonstrated how the reduction of uncorrelated noise provided by principal component analysis (PCA) can be exploited for automated alignment. PCA is an unsupervised multivariate technique that uses orthogonal linear transformations of the data onto a new coordinate system to project the greatest variance of the data onto the first component, the second greatest variance onto the second component, and so forth [11][12][13]. This processing extracts features with less uncorrelated noise from the datasets, thus allowing their automated alignment.…”
mentioning
confidence: 99%
“…The PCA and CA employed correlation ( =0.05) matrices on the variables in order to establish possible associations and input sources among polluting elements as described by Delgado, Nieto et al (2010). In PCA, the eigenvalues of the principal components are a measure of their associated variances (Meglen, 1992;Mellinger, 1987;Wenning and Erickson, 1994). Correlation of principal components and original variables is given by loadings.…”
Section: Discussionmentioning
confidence: 99%